A new way to carcinogenicity of azo dyes: the benzenediazonium ion formed from a non-aminoazo dye, 1-phenylazo-2-hydroxynaphthalene(Sudan I) by microsomal enzymes binds to deoxyguanosine residues of DNA - Stiborová, M; Asfaw, B; Anzenbacher, P; Hodek, P (Cancer letters, 1988)
1-Phenylazo-2-hydroxynaphthalene (Sudan I) activated by pre-incubation with microsomal enzymes of rat livers covalently binds to DNA from calf thymus. Benzenediazonium ion formed from Sudan I by activation with microsomal enzymes is the principal active metabolite, which binds to DNA. Enzymatic hydrolysis of modified (14C-labelled) DNA, followed by separation of deoxynucleosides on a Sephadex G-10 column revealed that deoxyguanosine is the principal target for the binding of activated Sudan I. The high-performance liquid chromatographic (HPLC) analysis indicate that probably more than one radioactive adduct of activated Sudan I with deoxyguanosine is formed.
Keywords: inbrední kmeny potkanů; karcinogeny; Microsomes, Liver; Rats, Inbred Strains; Rats; DNA; deoxyguanosin; mužské pohlaví; Chromatography, High Pressure Liquid; Naphthols; naftoly; diazoniové sloučeniny; vysokoúčinná kapalinová chromatografie; krysa rodu Rattus; biotransformace; Biotransformation; Animals; Diazonium Compounds; zvířata; Carcinogens; barvicí látky; jaterní mikrozomy; Coloring Agents; Male; Deoxyguanosine